The Development and Psychometric Assessment of Chinese Medication Literacy Scale for Hypertensive Patients (C-MLSHP) - Zhong, Zhuqing; Shi, Shuangjiao; Duan, Yinglong; Shen, Zhiying; Zheng, Feng; Ding, Siqing; Luo, Aijing (Frontiers in Pharmacology, 2020)
To develop the medication literacy scale for hypertensive patients, and to test the reliability and validity of the scale. Methods The initial draft of the scale was formulated based on a framework of medication literacy with four domains of knowledge, attitude, skill and practice. In this study, 260 patients with hypertension in Changsha, China were selected to conduct a pilot survey using the primary medication literacy scale. After item selection by a series of statistical analysis method, the scale was revised to form a formal investigation scale with 37 items. A formal investigation was carried out on 650 patients with hypertension selected purposively in a tertiary general hospital and two community health service centers in Changsha city of China. Results the formal scale consists of four domains on knowledge, attitude, practice and skills, 11 sub-factors and 37 items in total. S-CVI of the scale was 0.968, and the I-CVI for each item ranged from 0.833 to 1.000. The Cronbach’s α coefficient was 0.849 for the overall scale and ranged from 0.744 to 0.783 for domains. The Pearson’s correlation coefficients among domains and the total scale were ranging from 0.530-0.799. Besides, the Pearson’s correlation coefficient among domains of the scale ranged from 0.157 to 0.439. The split-half reliability coefficient was 0.893 for the total scale and ranged from 0.793 to 0.872 for domains. The test-retest reliability coefficient of the total scale was 0.968 and ranged from 0.880 to 0.959 for domains. Four domains of knowledge, attitude, skill and practice were identified. The total explained variation of domains for the overall scale was 51.420%. Eleven sub-factors for domains were extracted through exploratory factor analysis, and the total explained variation of sub-factors for each domain were ranging from 56.111%-64.419%. The confirmatory factor analysis showed the fit indices of the four-domain model were as follows (2/df=2.629，GFI=0.804，AGFI=0.777，RMR=0.012，IFI=0.746，RMSEA=0.066，PNFI=0.599，PCFI=0.689), which indicated an acceptable model fit. Conclusions The medication literacy scale for hypertensive patients has good reliability and acceptable validity. In the future, further model fit validation and English translation of this scale are required, so that this scale can be further validated and applied worldwide.